2007
DOI: 10.1038/sj.ejcn.1602971
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between long-chain polyunsaturated fatty acids at birth and motor function at 7 years of age

Abstract: Background/Objectives: Long-chain polyunsaturated fatty acids (LCPUFA) rapidly accumulate in the central nervous system (CNS) during the perinatal CNS growth spurt. This particularly concerns arachidonic acid (AA: 20:4nÀ6) and docosahexaenoic acid (DHA: 22:6nÀ3), which are thought to play important roles in CNS development and function. The aim of this study was to investigate the relation between motor function at 7 years of age and the levels of AA and DHA in umbilical venous plasma phospholipids, representi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 37 publications
1
25
0
3
Order By: Relevance
“…One study using cord blood data found a positive association between DHA levels and motor development (Bakker et al, 2009), while two other studies found no relationship with cognitive development (Bakker et al, 2003;Ghys et al, 2002). Regarding maternal fish consumption, findings from existing studies are more consistent by showing positive associations with child's psychomotor development (Daniels et al, 2004;Hibbeln et al, 2007;Oken et al, 2008).…”
Section: Introductionsupporting
confidence: 59%
“…One study using cord blood data found a positive association between DHA levels and motor development (Bakker et al, 2009), while two other studies found no relationship with cognitive development (Bakker et al, 2003;Ghys et al, 2002). Regarding maternal fish consumption, findings from existing studies are more consistent by showing positive associations with child's psychomotor development (Daniels et al, 2004;Hibbeln et al, 2007;Oken et al, 2008).…”
Section: Introductionsupporting
confidence: 59%
“…В другом когортном исследовании показано, что высокое содержание ДГК в сыворотке крови у женщин во время беременности сопровождалось такими благо-приятными эффектами у рождаемых детей, как более упо-рядоченный показатель структуры сна в раннем детстве [46], более успешная концентрация внимания в первые 2 года жизни [47], более высокая степень моторного раз-вития и меньшее число поведенческих проблем в воз-расте 7 лет [48]. Группой сравнения в этом исследовании служили дети, матери которых во время беременности дополнительно не получали ДГК.…”
Section: обзор литературыunclassified
“…Other studies did not show an association between DHA status at birth or intake during the first six months with cognitive performance at 4 or 7 yr of age (Bakker et al, 2003;Ghys et al, 2002), but a positive relationship with improved motor performance at 5 (Rask-Nissila et al, 2002) and 7 years of age (Bakker et al, 2009) (figure 2).…”
Section: Sensorimotormentioning
confidence: 99%
“…Five longitudinal studies, followed children form birth to childhood (Bakker et al, 2003(Bakker et al, , 2009Ghys et al, 2002;Gale et al, 2010) …”
Section: Evidence From Healthy Childrenmentioning
confidence: 99%